(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Tumor necrosis factor alpha (TNF?) induces insulin resistance in type 2 diabetes mellitus (T2DM). TNF-? -308G/A (rs1800629) polymorphism is associated with T2DM and its complications (particularly, diabetic retinopathy (DR) and diabetic maculopathy (DMP)) since it contributes to TNF-? expression. Purpose: To investigate the value of TNF-? (rs1800629) polymorphism in recurrent DMP after surgery in a Ukrainian population of patients with T2DM. Materials and Methods: The study included 313 patients with T2DM (313 eyes) and diabetic maculopathy. These included patients with mild nonproliferative DR (NPDR; n=40), moderate or severe NPDR (n=92), and proliferative DR (PDR; n=181). Patients received one of the four types of surgical treatment: only three-port closed subtotal vitrectomy (CSTV; n=78); CSTV combined with internal limiting membrane (ILM) peeling (n=85); CSTV combined with ILM peeling and panretinal laser coagulation (PRLC) (n=81); and CSTV combined with ILM peeling, PRLC and cataract phacoemulsification (phaco) (n=69). Baseline blood TNF-? levels were measured by enzyme-linked immunosorbent assay and rs1800629 was investigated by polymerase chain reaction. Statistical analyses were conducted using Statistica 10.0 (StatSoft, Tulsa, OK, USA) software. Results: In patients with DMP, rs1800629 was associated with the development and recurrence of DMP after surgery. Recurrent DMP developed in 96.9% of A/A genotype carriers. Heterozygous G/A genotype carriers had an increased risk (OR = 3.76; 95% CI: 2.27-6.27), whereas homozygous ancestral G/G genotype carriers, a decreased risk (OR = 0.02; 95% CI: 0.01-0.06) for recurrent DMP. TNF-? rs1800629 A-allele carriage was associated with macular edema. Among study patients, central retinal thickness was highest in A-allele carriers, both at baseline and after surgery, and did not decrease in these carriers within the follow-up period. Conclusion: An elevated TNF? blood level in carriers of the minor A-allele of the TNF? rs1800629 polymorphism was a factor promoting recurrent DMP after surgery.